1979
DOI: 10.1037/0096-3445.108.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Information processing in the cerebral hemispheres: Selective hemispheric activation and capacity limitations.

Abstract: Several previous experiments have found that concurrently maintaining verbal information in memory influences visual laterality patterns (e.g., Hellige & Cox, 1976; Kinsbourne, 1975). The present article critically reviews existing experiments and reports five additional experiments designed to identify the mechanisms responsible for such effects. Experiment 1 demonstrates that laterality patterns are not influenced by a concurrent memory task that does not require verbal processing. (The verbal nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(73 citation statements)
references
References 40 publications
(109 reference statements)
5
68
0
Order By: Relevance
“…If this capacity is occupied by concurrent tasks, then the subject's performance on the test task can be affected (Hellige, Cox, & Litvac, 1979;Moscovitch, 1979). It thus becomes important to consider what else the subject is doing during the experiment which might occupyhis right hemisphere's capacity.…”
Section: Discussionmentioning
confidence: 99%
“…If this capacity is occupied by concurrent tasks, then the subject's performance on the test task can be affected (Hellige, Cox, & Litvac, 1979;Moscovitch, 1979). It thus becomes important to consider what else the subject is doing during the experiment which might occupyhis right hemisphere's capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular design fluency tasks are primarily associated with the right frontal region (Ruff et al 1987), as is the left hand grip strength (Demaree et al 2002), map making, and facial affect recognition (Suberi and McKeever 1977). The right posterior region is associated with visuospatial praxis (Rao 2000), visuospatial memory (Hellige et al 1979), verbal prosody (Ross 2000), and facial recognition (Ekman and Friesen 1971). Conversely, the left hemisphere is typically associated with verbal fluency, speech production and reception (Damasio and Damasio 2000), and verbal memory (Max 2004).…”
Section: Functional Systemsmentioning
confidence: 99%
“…They found further support for the notion of sustained activational asymmetries between the hemispheres. Finally, in a series of experiments examining the effect of concurrent memory loads upon visual laterality patterns, Hellige, Cox, and Litvac (1979) have concluded that the hemispheres function as information processing systems that can be influenced somewhat separately from one another and can sustain different levels of activation. On the basis of these findings, it may be suggested that in the present paradigm the appearance of stimuli on one side or the other of the visual field serves to activate the contralateral hemisphere.…”
Section: Hemispheric Activationmentioning
confidence: 99%